Factors Affecting Tax Revenue at KPP Pratama Ternate City - Dwi Yana Amalia Sari Fala; Meliana Meliana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
Taxes have an important role in the life of the country and the implementation of development. Tax revenues are very much needed for this. Revenue that does not meet the target will certainly be an obstacle in the country's development process. The purpose of this research is to determine and analyze the influence of E-Commerce Transactions, Tax Audits, Information Technology, Account Representative Professionalism and E-Tax Applications on Tax Revenue at KPP Pratama Ternate City. The population in this study are individual taxpayers registered at KPP Pratama Ternate City. The sampling method used was simple random sampling. with a total sample of 399 respondents and using primary data. The test tool used is partial linear regression analysis (Partial Least Square/PLS). The research results show that e-commerce transactions have no effect on tax revenues. Meanwhile, audits, information technology, professionalism of account representatives and e-tax applications influence tax revenues.